High school teachers' skills in education (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article explains the main ideas about what teachers should be able to do. This text explains how a university teacher's skills and abilities are important in their role within the educational system and how it affects their interactions with students